The Correlation Between Students’ Internet Device Use and Language Literacy in Khalifah Model School Secondary - Kustina Sari, Neni; Herlinawati; Hafizah, Mardiah; Herdi (J-SHMIC : Journal of English for Academic, 2026)
In the current era of globalization, technology plays an important role in all parts of life, especially in the world of education which is used to improve the teaching and learning process in the classroom. The increased use of technology in education will greatly help students and teachers in completing tasks while expanding their knowledge and understanding through the use of existing technology. This study aims to investigate the correlation between students' use of internet devices and language literacy at Khalifah Model School Secondary Malaysia. This study used quantitative method with a correlation design to assess the relationship of students' internet device use and language literacy. Data was collected through two sets of questionnaires with a total of 35 questions, which were administered to Grade 8 and 9 students with a total sample of 61 students. The results showed that there was a correlation between students' internet device use and language literacy (sig. 2 tailed = 0.005 < 0.05). However, the Pearson correlation coefficient of -0.356 indicates a negative relationship with low strength. In conclusion, this study found there is correlation but not significant between language literacy and internet use among schoolchildren. This study implies the need for a more thoughtful and targeted approach in integrating technology into education to maximize its benefits for students' literacy. This will be potential for the future researchers to investigate more topics about the school students’ literacy and internet usage in the contexts of classroom settings.